Control of three dimensional particle flux to divertor using rotating RMP in the EAST tokamak. (26th February 2018) - Jia, M.; Sun, Y.; Liang, Y.; Wang, L.; Xu, J.; Gu, S.; Lyu, B.; Wang, H.H.; Yang, X.; Zhong, F.; Chu, N.; Feng, W.; et al.
Abstract: Controlling the steady state particle and heat flux impinging on the plasma facing components, as one of the main concerns of future fusion reactors, is still necessary when the transient power loads induced by edge localized modes (ELMs) have been eliminated by resonant magnetic perturbations (RMPs) in high confinement tokamak experiments. This is especially true for long pulse operation. One promising solution is to use the rotating perturbed field. Recently rotating and differential phase scans of n   =  1 and 2 RMP fields have been operated for the first time in EAST discharges. The particle flux patterns on the divertor targets change synchronously with both rotating and phasing RMP fields as predicted by the modeled magnetic footprint patterns. The modeling with plasma response, which is calculated by MARS-F, is also carried out. The plasma response shows amplifying or screening effect to n   =  2 perturbations with different spectra. This changes the field line penetration depth rather than the general footprint shape. This has been verified by experimental observations on EAST. These experiments motivate further study of reducing both transient and steady state local power load and particle flux with the help of rotating RMPs in long pulse operation.